Analisis Implementasi Teknologi Informasi terhadap Audit Internal dan Pengendalian Internal Bank SulutGo - Mukarromah Maulidah Raudhatul Jannah; Indira Rizqi Ardhiani Widodo; Sheryl Amanda Surjono (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2021)
All areas of human life have been entered by information technology, including the internal audit and internal control of a company. This research expects to decide the impact of data innovation on inner review and interior control at Bank SulutGo. This research uses a qualitative method with a literature study approach. The results obtained are that information technology has an effect on internal audit and internal control of Bank SulutGo. The audit process of Bank SulutGo has developed its information technology by creating an internal audit system based on the Auditing Through the Computer method. Bank SulutGo's internal control is also developed in accordance with the development of information technology as evidenced by manually or computer data archives and using the OLIBS (On Line Integrated Banking System) system. The practical impact that can be felt from this research is that it becomes an evaluation material for Bank SulutGo to continue to improve information technology in relation to internal audit and internal control. Keywords: Information Technology, Internal Audit, Internal Control